Gut microbiota and eye diseases: a bibliometric study and visualization analysis - Fu, Xiangyu; Tan, Haishan; Huang, Ling; Chen, Wenyue; Ren, Xiang; Chen, Danian (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Recently the role of gut microbial dysbiosis in many ocular disorders, including but not limited to uveitis, age-related macular degeneration (AMD), diabetic retinopathy (DR), dry eye, keratitis and orbitopathy is a hot research topic in the field. Targeting gut microbiota to treat these diseases has become an unstoppable trend. Bibliometric study and visualization analysis have become essential methods for literature analysis in the medical research field. We aim to depict this area's research hotspots and future directions by bibliometric software and methods. Methods We search all the related publications from the Web of Science Core Collection. Then, CiteSpace was applied to analyze and visualize the country distributions, dual-map overlay of journals, keyword bursts, and co-cited references. VOSviewer was employed to identify authors, co-cited authors, journals and co-cited journals and display the keyword co-occurrence networks. Results A total of 284 relevant publications were identified from 2009 to 2023. The number of studies has been small in the first five years and has grown steadily since 2016. These studies were completed by 1,376 authors from 41 countries worldwide, with the United States in the lead. Lin P has published the most papers while Horai R is the most co-cited author. The top journal and co-cited journal are both Investigative Ophthalmology & Visual Science. In the keyword co-occurrence network, except gut microbiota, inflammation becomes the keyword with the highest frequency. Co-citation analyses reveal that gut dysbiosis is involved in common immune- and inflammation-mediated eye diseases, including uveitis, diabetic retinopathy, age-related macular degeneration, dry eye, and Graves' orbitopathy, and the study of microbiomes is no longer limited to the bacterial populations. Therapeutic strategies that target the gut microbiota, such as probiotics, healthy diet patterns, and fecal microbial transplantation, are effective and critical to future research. Conclusions In conclusion, the bibliometric analysis displays the research hotspots and developmental directions of the involvement of gut microbiota in the pathogenesis and treatment of some ocular diseases. It provides an overview of this field's dynamic evolution and structural relationships.